2022
DOI: 10.3390/foods11213535
|View full text |Cite
|
Sign up to set email alerts
|

Different Structures of Arabinoxylan Hydrolysates Alleviated Caco-2 Cell Barrier Damage by Regulating the TLRs/MyD88/NF-κB Pathway

Abstract: Arabinoxylan (AX) has been associated with alleviating intestinal barrier damage, and different structures of AX give rise to different effects on the intestinal barrier. This study investigated the main structural characteristics of AX, whose functional properties are attributed to alleviating intestinal barrier damage, and clarified their underlying mechanisms. An in vitro Caco-2 cell model was established to investigate the intestinal barrier effects of AX with various degrees of substitution (Ds) and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Once internalized, β-glucan containing macrophages migrate to the spleen, lymph nodes, and the bone marrow where immune modulation takes place ( Hong et al, 2004 ). Consistent with previous studies ( Baggio et al, 2022 ; Li et al, 2022 ), arabinoxylan preparations showed a clear effect on barrier integrity in our study, with the smaller particle size fractions of rice bran-1 increasing TEER. Interestingly, we demonstrated that apical exposure to smaller rice bran-1 particle fractions of 106–90 and 90-45 μm in the co-culture model elicits a strong induction of both innate immune training and resilience, as measured by the increased release of TNF-α.…”
Section: Discussionsupporting
confidence: 93%
“…Once internalized, β-glucan containing macrophages migrate to the spleen, lymph nodes, and the bone marrow where immune modulation takes place ( Hong et al, 2004 ). Consistent with previous studies ( Baggio et al, 2022 ; Li et al, 2022 ), arabinoxylan preparations showed a clear effect on barrier integrity in our study, with the smaller particle size fractions of rice bran-1 increasing TEER. Interestingly, we demonstrated that apical exposure to smaller rice bran-1 particle fractions of 106–90 and 90-45 μm in the co-culture model elicits a strong induction of both innate immune training and resilience, as measured by the increased release of TNF-α.…”
Section: Discussionsupporting
confidence: 93%
“…MYD88 tissue factor induces p65 translocation by TLR receptors [12]. TLR activation induces cytokine release, which is confirmed by our TNF-α, IFN-γ, and IL-8 results [38]. Anthocyanin treatment significantly reduced the translocation of p65 in our experiments, but alone, AC treatment did not result in any alteration in NF-κB activation (Figure 4b).…”
Section: Discussionsupporting
confidence: 82%
“…TLRs are phylogenetically conserved innate immune mediators that can identify gut microbiota and respond to harmful microbes [78,79]. TLR2 and TLR4 are two important members of TLRs, which participate in the immune response mainly by activating the MyD88 pathway to induce the secretion of inflammatory cytokines [51,58,80]. MyD88 is a key adapter protein in the TLR signaling pathway that can activate NF-κB, boosting the production of proinflammatory cytokines and eliciting an immunological response in the intestinal mucosa [51,81].…”
Section: Clostridium Butyricum and Intestinal Immune Barriermentioning
confidence: 99%